Kontribusi Sosial Mahasiswa KKN UINFAS Bengkulu Dalam Kegiatan Pengabdian Di Lagan Bungin Kabupaten Bengkulu Tengah - Ayu Yeri Andira; Dewi Sintah; Diana Pratiwi; Elpita Sari; Fiter Stiawan; Hartono Bahri; Joviyon Memettoso; Seva Fadillah; Siska Niken Prahayu; Weta Fransiska (Pakis Journal Institute, 2024)
The Kuliah Kerja Nyata (KKN) program for students at Universitas Islam Negeri Fatmawati Soekarno Bengkulu (UINFAS) serves as a means for students to carry out community service projects. The purpose of this service is to assist the community through activities that are demonstrably beneficial to the community. Kegiatan di Kabupaten Bengkulu, Desa Lagan Bungin. The activities include observation, mass khitanan, active participation in the Republik Indonesia (RI) Day celebrations, assisting children in reading in the mosque and learning at MI Assalam Terpadu. This KKN exercise is very beneficial because through it, students can apply their knowledge, understand how to live together in the community, and become more confident in their ability to communicate.